Relationship between Blood Sugar Levels and People's Consumption Patterns of Bandar Lampung - Saputri, Dwijowati Asih; Novitasari, Aulia (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Blood sugar is important for the body, unstable blood sugar can cause low blood sugar levels (hypoglycemia) or high blood sugar levels (hyperglycemia) which is one sign of diabetes mellitus. The wrong consumption pattern, malnutrition, or obesity (overweight) can cause the risk of diabetes mellitus, poor nutrition can damage the pancreas, while excess obesity can interfere with the work of the insulin hormone. The purpose of this research is to determine the relationship between blood sugar levels and consumption patterns of people in Bandar Lampung City. This research method is quantitative with cross sectional design. The research was conducted in 20 sub-districts in Bandar Lampung City, with a sampling technique that is stratified random sampling. The data collection technique was carried out by taking blood samples for checking blood sugar levels followed by filling out the consumption pattern questionnaire by the respondents.